"With courage against the system." The ideology of the people's party our Slovakia. (2nd September 2022) - Drábik, Jakub
ABSTRACT: The Kotleba – People's Party Our Slovakia (LSNS) was founded in 2010 and has been the centre of attention from Slovak media, academia and politicians since 2013. In spite of this interest, there appears to be no consensus in the way that it should be referred to – is it a neo-fascist, a neo-Nazi or a radical right-wing party? The aim of this study is an attempt to analyse the ideology of the LSNS based on both official and unofficial statements and the rhetoric of its representatives, the party's agenda and propaganda. It argues that the party´s past, its constant attacks on democracy and the democratic system, the glorification of undemocratic regimes, declared efforts to achieve an "alternative to the contemporary decadent era, " and a "new epoch, " its international cooperation with similar movements, racists, anti-Semitic statements and the use of neo-Nazi symbolism indicate the neo-Nazi character of the party's ideology.